2017
DOI: 10.1057/s41287-017-0103-6
|View full text |Cite|
|
Sign up to set email alerts
|

Men’s Involvement in a Parenting Programme to Reduce Child Maltreatment and Gender-Based Violence: Formative Evaluation in Uganda

Abstract: Parenting programmes involving fathers can reduce child maltreatment and gender-based violence. However, most parenting programmes find it difficult to recruit fathers. We piloted a 21 session parenting intervention, ‘Parenting for Respectability’, with fathers and mothers near Kampala, Uganda. Sixty-one fathers and 83 mothers were recruited initially and 52 fathers and 76 mothers retained to the end. We interviewed with 24 fathers and 16 mothers. Data were analysed thematically. Success in involving fathers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 47 publications
(57 reference statements)
0
48
0
Order By: Relevance
“…However, quantitative evaluation of the same intervention showed a non-significant increase,72 while two quantitative studies of participatory women’s groups found little evidence for impact on household agency 81 82. A qualitative study of an intervention to engage fathers in group discussion found that it actually entrenched patriarchal norms by encouraging husbands to police their wives’ behaviour in accordance with advice from facilitators 54. We found no study linking women’s position in the household to health outcomes or behaviours in an intervention context.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, quantitative evaluation of the same intervention showed a non-significant increase,72 while two quantitative studies of participatory women’s groups found little evidence for impact on household agency 81 82. A qualitative study of an intervention to engage fathers in group discussion found that it actually entrenched patriarchal norms by encouraging husbands to police their wives’ behaviour in accordance with advice from facilitators 54. We found no study linking women’s position in the household to health outcomes or behaviours in an intervention context.…”
Section: Resultsmentioning
confidence: 99%
“…Group deliberation : Qualitative evidence indicated that group members frequently shared in meetings experiences, concerns and opinions about both their own health issues and wider problems in the community,37 48–55 a process that might facilitate the development of critical consciousness 37. It might also help group members pool individual pieces of knowledge into a more accurate, collective understanding of health53 and decide on and plan solution strategies 48 56…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This likely has to do with the social norms of women bearing the responsibility for childcare. Engaging men in parenting interventions requires a conscious effort in program design and delivery, such as drawing on specific motivations for fathers (Siu et al 2017 ). In addition, children attended more sessions than caregivers, but had a lower average engagement in sessions, perhaps due to the cultural norms mandating that children show respect to elders.…”
Section: Discussionmentioning
confidence: 99%